The effect of interface roughness scattering on Si SOI FinFET with Ando's and extended Prange and Nee model. (September 2015) - Nagy, D; Elmessary, M A; Aldegunde, M; Kalna, K
Abstract: A new multi-subband interface roughness scattering (IRS) model is incorporated into a 3D Finite Element Monte Carlo simulator with 2D Schrödinger equation based quantum corrections. The model takes advantage of wavefunctions and energy levels obtained in solutions of Schrödinger equation on slices across the channel to calculate the respective form factors. The new 3D code is then used to forecast the performance of 10.7 nm gate length SOI Si FinFETs with rectangular cross-section and rounded corners. We found that the multi-subband IRS is much stronger at large electron kinetic energies resulting in a drive current of 600 mA/μm 2 that is 25% reduction when compared to 3D Ando model.